MANAGEMENT OF FIBULAR HEMIMELIA (CONGENITAL ABSENCE OF FIBULA) USING ILIZAROV METHOD IN SULAIMANI - Barawi, Omer Ali Rafiq; Amen, Zmnako J. (European Scientific Journal, ESJ, 2015)
Background: Fibular hemimelia is the most common congenital deficiency of long bones. Therefore, it is characterized by a wide spectrum of manifestations ranging from mild limb length inequality to sever shortening with foot and ankle deformities and associated anomalies. Objectives: To evaluate the results of ankle and foot reconstruction and limb length equalization in patients with Fibular Hemimelia. Patients and Methods: A prospective study was carried out on 40 limbs in 32 patients with fibular hemimelia during the periods of March 2010 to January 2014. Male to female ratio was 24:8. Their age ranged at an average between 2-16 years (9 years). The reconstruction of ankle and foot was done. Also, the equalization of the limb was done also using Ilizarov frame. Results: The result of this study was assessed using the Association for the Study of Applications of Methods of Ilizarov (ASAMI) scoring system. Therefore, the final results were: Failure rate with 2 limbs 5%, Poor with 2 limbs 5%, Fair with 2 limbs 5%, Good with 8 limbs 20%, and Excellent with 26 limbs 65%. Conclusion: In conclusion, the Ilizarov method is an attractive alternative method used for the management of selected fibular hemimelic patients having three or more toes who are refusing amputation.